Efisiensi Kinerja Traktor Singkal dan Traktor Rotari pada Pengolahan Tanah di Subak - I Wayan Tika; Sumiyati; Ni Nyoman Sulastri; Ida Ayu Gede Bintang Madrini; Mentari Kinasih (Jurnal BETA (Biosistem dan Teknik Pertanian), 2023)
Before Subak farmers were familiar with tractors, land preparation was carried out using hoes or single-handed plows pulled by cattle. Land preparation with a tractor equipped with a complementary or rotary plow cannot be avoided in cases of overlap of processing results so that the processed soil results become inefficient. The overlapping results of the processing can be seen from the differences in the results of the processed soil. Based on these conditions, it is necessary to study the efficiency of tillage in Subak using single-axle tractors and rotary tractors in the first stage of tillage. Tractor work efficiency is measured based on a comparison between theoretical work and real work. Theoretical work is measured based on the width of the complement of the tiller, both short and rotary plows, and the average speed of the tractor's advance when cultivating the land. Real work is measured based on real work results in the field, namely the area ofland that has been successfully processed within a certain time span. Real work data was also confirmed based on the results of discussions with several tractor operators. From the results of the data analysis, it was obtained that the work efficiency of the short tractor was 77.3% and that of the rotary tractor was 55.2%.